Optimization of Patrol Implementation by the Sat Samapta Unit to Prevent Motor Vehicle Theft in the Area of Semarang Polrestabes - Salsabila, Salsabila (Advances in Police Science Research Journal, 2024)
The author raised the final task with the problem of “Optimization Patrol Implementation of The Samapta Unit Patrol To Prevent The Crime of Motor Vehicles Theft In The Area of Semarang Polrestabes”. This final task was made with the aim to identify the implementation of patrol by the samapta unit turjawali of the Semarang Polrestabes and to identify the optimization of patrol by the samapta unit turjawali of the Semarang Polrestabes. In this final task, the author uses a qualitative approach with this type of field research by conducting resource interviews, observations, and document studies. In addition, the data used is also obtained from various references such as articles, news and online media that are relevant to the variable problems discussed In addition, the data used is also obtained from various references such as articles, journal books and online media news that are relevant to the variable problems discussed. This research uses organizational resource theory, management theory, and SWOT analysis theory and several concept that relevant to the variable, namely concept of optimization, concept of patrol, concept of samapta, and concept of motor vehicles theft. The Semarang Polrestabes Samapta unit is the sprearhead of preventive police action in preventing criminal acts especially motor vehicles theft in the Semarang Polrestabes jurisdiction. In the implementations of patrol, there are still found some shortcomings in terms of organizational resource, terms of planning, organizing, implementation and and not in accordance with the Patrol SOP that has been regulated in Perkabaharkam Number 1 of 2017 concerning Patrols. In addition, the existence of factor that affect both internally and externally makes the implementation of patrol of the Polrestabes Semarang Samapta Unit Turjawali cannot be carried out optimally. On the other hand, to improve the implementation of patrols, creative breakthroughs are needed in efforts to improve patrol implementation.